HUBUNGAN ANTARA TINGKAT PENDIDIKAN IBU DENGAN PERKEMBANGAN BALITA USIA 3-5 TAHUN (SUATU STUDI DIKELURAHAN KADIPATEN KECAMATAN BOJONEGORO KABUPATEN BOJONEGORO TAHUN 2014) RELATIONSHIP BETWEEN EDUCATION LEVEL MOTHER WITH TODDLER DEVELOPMENT AGE 3-5 YEARS ( - HIDAYAH, WAQIDIL; CK, ADINI (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2016)
Education about early childhood development is a process of changing the personality, attitude and understanding about appropriate development for toddlers. The lack of knowledge becomes a major causal factor in the failure of early childhood development, for example, mothers with low education then it will be difficult to digest the message delivered to educate a child in foster toddler. The purpose of this study was to analyze the relationship between mother's education level with 3-5 years of early childhood development. This study is a correlation study using cross-sectional approach. The population is mothers and toddlers 3-5 years as many as 42. Technique used is total sampling. Data collection by questionnaire and observation (DDST) and then do the editing, coding, scoring, tabulating and analyzing statistical data using Spearman's test (? <0.05), the results of the study are presented in the form of images, tables and narrative.Both of these variables were tested by using analysis of the significance of a cross table with the value of ?: ? value of 0.05 obtained: 0.000 <? 0.05, so Ho is rejected, which means there are relations Education Level Mother With Toddler Development (3-5 years) in the Village Kadipaten District of Bojonegoro 2014.The conclusion of this study is the education level of respondents no association with the development of toddlers 3-5 Years in the Village Kadipaten District of Bojonegoro 2014. Respondents continued attitude they have to educate early childhood development and mutual information or the exchange of experience with other respondents so as to increase better knowledge.